2012
DOI: 10.1038/modpathol.2012.141
|View full text |Cite
|
Sign up to set email alerts
|

Activity and complexes of mTOR in diffuse large B-cell lymphomas—a tissue microarray study

Abstract: Diffuse large B-cell lymphoma is a heterogeneous group of diseases with different responses to therapy. Targeting mTOR (mammalian target of rapamycin) offers a new approach to improve the treatment. mTOR inhibitors are being developed and are in clinical use in mantle cell lymphoma therapy and clinical trials are ongoing in other high-grade lymphomas as well. However, there is limited data about mTOR activity and the expression of its different complexes in diffuse large B-cell lymphomas. Tissue microarray blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
3
24
1
Order By: Relevance
“…Activation of the mTOR pathway has been shown previously in DLBCL, although not in the cell lines used herein, and a recent study has also reported activation of mTOR in a subset of DLCBL patients. 36 Moreover, eIF4B was present on two lists of genes whose expression changed following mTOR inhibition. 37, 38 Therefore, DLBCL and control cells were immunoblotted to assess the expression and phosphorylation status of protein kinase B/AKT, mTOR and 4EBP1.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the mTOR pathway has been shown previously in DLBCL, although not in the cell lines used herein, and a recent study has also reported activation of mTOR in a subset of DLCBL patients. 36 Moreover, eIF4B was present on two lists of genes whose expression changed following mTOR inhibition. 37, 38 Therefore, DLBCL and control cells were immunoblotted to assess the expression and phosphorylation status of protein kinase B/AKT, mTOR and 4EBP1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies examining the role of mTOR partners', raptor and rictor, in predicting responders are planned for the future. 11 Clinical studies are also underway evaluating mTOR-directed therapy earlier in the course of this disease and in combination with additional agents to overcome resistance thought to occur through escape via the AKT pathway. These studies are likely to identify responders to this therapy and to improve outcomes for patients with resistant DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that patients with poor prognosis may be identified by measuring p-4EBP1 levels at diagnosis; further markers will be required for predicting the potential response to rapamycin treatment for individual patients within this group. Indeed, it must be kept in mind that high basal mTORC1 activity does not necessarily mean that the patient will respond to MTIs [45]. Our results demonstrate that in vitro rapamycin treatment does not necessarily result in the decrease of mTOR activity in ALL cells in all cases.…”
Section: Discussionmentioning
confidence: 72%